1993
DOI: 10.1073/pnas.90.16.7819
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-aspartate receptors are clustered and immobilized on dendrites of living cortical neurons.

Abstract: The response of nerve cels to synaptic inputs and the propagation of this activation is critically dependent on the cell-surface distribution of ion channels. In the hippocampus, Ca2+ influx through N-methyl-D-aspartate receptors (NMDAR) and/or voltage-dependent calcium channels on dendrites is thought to be critically involved in long-term potentiation, neurite outgrowth, epileptogenesis, synaptognesis, and cell death. We report that conantokin-G (CntxG), a peptide from Conus geographus venom, competitively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 27 publications
4
37
0
2
Order By: Relevance
“…The significant block of the stereocilia TNP-ATP binding (57%) by suramin is highly suggestive of specific binding of the TNP-ATP to P, purinoceptors localized to this region. The level of block obtained with suramin is comparable .to that achieved in a recent imaging study localizing NMDA receptors to isolated neurons (Benke et al, 1993) utilizing a fluorescent derivative of conotoxin-G (CntxG), with specific block achieved with a thousand-fold excess of native CnTxG. In the present study, a caveat to the evidence for P, purinoceptor localization to the stereocilia of hair cells is the possibility of undetermined (nonspecific) interactions of TNP-ATP with the glycocalyx of the hair cells, given previous evidence for attraction of charged molecules by this region (see Santi and Anderson, 1987, for a review).…”
Section: Discussionsupporting
confidence: 59%
“…The significant block of the stereocilia TNP-ATP binding (57%) by suramin is highly suggestive of specific binding of the TNP-ATP to P, purinoceptors localized to this region. The level of block obtained with suramin is comparable .to that achieved in a recent imaging study localizing NMDA receptors to isolated neurons (Benke et al, 1993) utilizing a fluorescent derivative of conotoxin-G (CntxG), with specific block achieved with a thousand-fold excess of native CnTxG. In the present study, a caveat to the evidence for P, purinoceptor localization to the stereocilia of hair cells is the possibility of undetermined (nonspecific) interactions of TNP-ATP with the glycocalyx of the hair cells, given previous evidence for attraction of charged molecules by this region (see Santi and Anderson, 1987, for a review).…”
Section: Discussionsupporting
confidence: 59%
“…The demonstration of NMDA receptor channels in the dendrites of CA3 pyramidal neurons was surprising in view of the fact that binding studies had indicated that these dendrites are devoid of NMDA receptors in the region of MF termination (Monaghan, Holets, Toy & Cotman, 1983;Benke, Jones, Collingridge & Angelides, 1993 (Jahr, 1992;Rosenmund, Clements & Westbrook, 1993;Hessler, Shirke & Malinow, 1993), and a mean quantal conductance change of 350 pS for the AMPA receptor-mediated EPSC (Jonas et al 1993). Assuming that the glutamate pulse in the synaptic cleft is roughly equivalent to the 1 ms pulse of 1 mim glutamate used in the present experiments (Clements et al 1992;see Jonas & Spruston, 1994 (Silver, Traynelis & Cull-Candy, 1992;Stern et al 1992b).…”
Section: Discussionmentioning
confidence: 99%
“…MCPG is a broadly acting blocker for different types of metabotropic glutamate receptors. AMPA as well as NMDA receptors are located on the postsynaptic site of synapses (Benke et al, 1993;Craig et al, 1993), and they mediate postsynaptic transmission in the hippocampus (Bekkers and Stevens, 1989). Metabotropic glutamate receptors are present on the postsynaptic membrane, and their activation or blockade can alter calcium levels within hippocampal neurons (Baude et al, 1993;Frenguelli et al, 1993).…”
Section: Spinesmentioning
confidence: 99%